ANALISIS PENGARUH NON PERFORMING LOAN, RETURN ON ASSET, DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL TERHADAP PEROLEHAN LABA - Nadabila Zahra; R. Deni Muhammad Danial; Dicky Jhoansyah (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
The objectives of this study are 1) To find out how the analysis of non-performing loans, return on assets, operating costs and operating income and profit generation in 2019-2021. 2) To find out whether non-performing loans can affect profit generation in 2019-2021. 3) To find out whether return on assets has an effect on profit earning in 2019-2021. 4) To find out whether operating costs and operating income on profit generation in 2019-2021. 5) To find out how the effect of non-performing loans, return on assets, operating costs and operating income on profit generation in 2019-2021. The research method that researchers use in solving problems is quantitative methods. The population in this study are all companies included in Commercial Bank Companies listed on the Indonesia Stock Exchange from 2019 to 2021. the results of this study are Non-performing loans on earnings have a significant effect. This is indicated by t count greater than t table. Return on assets on profit does not have a significant effect. This is indicated by t count smaller than t table. Operating costs of operating income on profitability have a significant influence. This is indicated by t count greater than t table.